Establishment of a new cell line of canine inflammatory mammary cancer: IMC‐118. (25th May 2022) - Gao, Hongbo; Zhou, Han; Gao, Yiming; He, Lixin; Li, Wenxuan; Xu, Meixia; Feng, Huili; Feng, Xiujuan; Qiu, Changwei
Abstract: Canine inflammatory mammary cancer (IMC) has long been regarded as an attractive animal model for research into human inflammatory breast cancer (IBC), Although some canine mammary tumour cell lines corresponding to human mammary cancer cell lines have been established, there is still a need to supplement the canine mammary tumour cell bank. The goal of this study was to create a new type of IMC cell line. The primary tumour, IMC‐118, was identified as IMC by pathology examination. Immunohistochemistry analysis revealed negative immunoreactivity to oestrogen receptor (ER), but positive immunoreactivity to progesterone receptor (PR) and human epidermal growth factor receptor‐2 (HER‐2). Immunofluorescence (IF) analysis revealed that the IMC‐118 cell line from this primary tumour was negative for ER but positive for PR and HER‐2, and was also positive for epithelial and mesenchymal cell markers. This cell line was cultured stably for more than 50 passages and grew well after cryopreservation. In vivo, tumour masses and metastases in the lungs were discovered after inoculating the IMC‐118 cells into the nude mice model. As a result, a novel canine IMC cell line, IMC‐118, was effectively established, and could be employed as a promising model for immunotherapy and epithelial‐mesenchymal transition mechanism of IMC research in both dogs and humans.